Pengaruh Penerapan Model Pembelajaran Roda Keberuntungan Terhadap Pemahaman Konsep Matematis Siswa Kelas IX SMPN 3 Koto Baru Kab. Dharmasraya - Rahmi, Rahmi; Diana, Yhance Hendra (Prodi Pendidikan Matematika, 2013)
This research has background of the problem because of learning outcome of students math is under of minimum criteria. Teaching and learning process is monotonous so the students are bored in learning. This research has purposes: 1) to know is understanding of students math concept by using teaching and learning method of âRoda Keberuntunganâ is betten than by using teaching and learning conventional; 2) to know indicator achievement of understanding of students math concept at IX grade of SMPN 3 Koto Baru Kab. Dharmasraya in academic year 2011-2012.Type of this research is experimental research is experimental, with totaly of students population is IX grade SMPN 3 Koto Baru in academic year 2011-2012. The sample are class IXA and IXB. The Instrumentation is used test understanding of concept and quiz. It is using essay test that has indicator of concept understanding with reliability 0.864.Based on research finding is gotten meanscore of understanding test of students math concept atv experimental class is 80.33 and control class is 68.73. Hypothesis testing used t-test by using software minitab, it is gotten P-value (0.000) less than Î± (0.05) so hypothesis is accepted with 95%. In Conclusion, understanding of students math concept by using âRoda Keberuntunganâ method is better than understanding of students mat concept by using conventional method. Based on data analysis of quiz is gotten that has increasing on indicator understanding of students math concept for every meeting by using âRoda Keberuntunganâ.Key Word: Roda Keberuntungan, Pemahaman Konsep matematis